CRITERIA FOR RUPTURE OF AMNIOTIC FLUID IN WOMEN OF REPRODUCTIVE AGE - Khatamova Matluba Tilavovna; Sharopova Gulnigor Kuntug’mish qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Summary. The combination of prenatal amniotic fluid and infectious diseases is a serious problem in modern obstetrics. The causes of prenatal rupture of amniotic fluid, despite numerous studies, have not been definitively established, although infection is considered to be the leading factor in this complication.